Promosi Ruang Kreatif Ekologis dan Camp Education (Riverside Camp Kota Metro) - Misfi Laili Rohmi; Rista Meilia; Trio Fajri; Husna Nur Pujianto; Carmidah Carmidah (Universitas Kristen Indonesia Toraja, 2024)
Tourism that carries the theme of nature is currently showing a stretch of development. Tourist attractions are starting to move to present green open spaces designed in such a way as to attract visitors. One of the eco-based tourist attractions in Metro City is Riverside Camp. Riverside Camp is an ecological-based educational vehicle in Metro City with the concept of ecological tourism as well as education-based tourism that has economic potential. However, since the Covid-19 pandemic container, Riverside Camp has seemed to be in “suspended animation” so it needs a touch to make it come back to life. Thus, the purpose of this service is to reintroduce Riverside Camp to the community through various activities which will later be shared on social media. The method of implementing the service begins with a discussion with the service team consisting of two lecturers and three accompanying students with 40 student service participants. Next is coordination with the manager to plan a schedule of activities. This service was carried out for four days with the result that the participants had the opportunity to learn about digital marketing in the open space of the Riverside Camp; implementation of activities to introduce trigona honey bee cultivation and planting several types of plants with polygonal media; as well as participants and the service team were able to make Riverside Camp promotional media through the Instagram page.